The Aeroplane - Grahame-White, Claude, 1879-1959; Harper, Harry, 1880-1960 (Salt Lake City, UT : Project Gutenberg, 2014)
"The Aeroplane" by Claude Grahame-White and Harry Harper is a historical account likely written in the early 20th century. The book explores the evolution of aviation, detailing the journey from primitive flight attempts to the successes of notable inventors and aviators, emphasizing the human stories and challenges behind the technological advancements. It delves into the lives and contributions of pioneering figures like Otto Lilienthal and the Wright brothers, making it a fascinating read for those interested in the history of flight and the determination of early aviation pioneers. The opening of the book sets the stage for a comprehensive chronicle of flight's history, outlining its progression in five distinct stages$1 (Bfrom rudimentary, hazardous trials to more scientific approaches to flight. It begins with references to early attempts by individuals like Simon the magician and a monk named Elmerus, emphasizing the desperation and folly of their efforts. The authors then transition into discussing the groundwork laid by scientists who studied birds and developed theories on flight. Through this introduction, the narrative hints at the human narratives behind aviation's development, showcasing the ambition and perseverance of those who faced ridicule and failure on their path to achieving powered flight. (This is an automatically generated summary.)s
Release date is 2014-05-30
E-text prepared by Charlene Taylor, Paul Marshall, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive/American Libraries (https://archive.org/details/americana)
Keywords: Airplanes; Aeronautics